2015
DOI: 10.3389/fvets.2015.00014
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potential Biomarkers for Gut Barrier Failure in Broiler Chickens

Abstract: The objective of the present study was to identify potential biomarkers for gut barrier failure in chickens. A total of 144 day-of-hatch Ross 308 male broiler chickens were housed in 24 battery cages with six chicks per cage. Cages were randomly assigned to either a control group (CON) or gut barrier failure (GBF) group. During the first 13 days, birds in CON or GBF groups were fed a common corn–soy starter diet. On day 14, CON chickens were switched to a corn grower diet, and GBF chickens were switched to rye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
166
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(181 citation statements)
references
References 105 publications
(131 reference statements)
11
166
1
3
Order By: Relevance
“…Therefore, it is possible that Thai-breed chickens might be affected by fasting (12 h) before sample collection, which caused a reduction in the mucin intestinal surface and intestinal morphology. Different types of diets can affect the intraluminal milieu by disturbing the digestive viscosity and mucins (7). However, all chickens in our study were fed the same diet and nutrients to reduce the effect of dietary factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is possible that Thai-breed chickens might be affected by fasting (12 h) before sample collection, which caused a reduction in the mucin intestinal surface and intestinal morphology. Different types of diets can affect the intraluminal milieu by disturbing the digestive viscosity and mucins (7). However, all chickens in our study were fed the same diet and nutrients to reduce the effect of dietary factors.…”
Section: Discussionmentioning
confidence: 99%
“…Claudin and occludin proteins are mainly responsible for intestinal barrier function and paracellular diffusion (1,7,8,19). Claudin-1 proteins are constantly expressed in the intestinal lining from the hatching period to the formation of adult chickens (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that poor gut health due to the disruption of the intestinal barrier, such as the one triggered by Eimeria, causes an undesirable impact in health and growth performance of broiler chickens (Chen et al 2015). Inflammatory responses and gut disorders in broilers have economic consequences, such as a decrease in body weight gain and overall performance of the flock (Van Leeuwen et al 2004;Shirzadi et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…본 실험에서 처 리구와 대조구간의 지방산패도의 유의적 차이는 나타나지 않았다(P>0.05). Aengwanich and Suttajit(2010) (Song et al, 2014;Chen et al, 2015). Fig.…”
unclassified